1974
DOI: 10.1111/j.1440-1681.1974.tb00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of the Sympathomimetic Bronchodilator, Trimetoquinol (Aql 208) on the Cardiac, Respiratory and Skeletal Muscle Systems in the Anaesthetized Cat, and on Cat Isolated Atrial and Tracheal Preparations

Abstract: S U M M A R Y1. The actions of the sympathomimetic bronchodilator trimetoquinol (AQL 208) have been compared with those of laevoisoprenaline on the cardiac, respiratory and skeletal muscle systems of the cat under chloralose anaesthesia, and on cat isolated atrial and tracheal preparations.2. Trimetoquinol injected intravenously ranged in potency from two to four times less potent to about four times more potent than laevoisoprenaline in different in vivo experiments. Despite such wide variations in absolute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…Other workers have found that the selectivity of P2adrenoceptor agonists is lower in the cat than in other laboratory species, for example the guinea-pig (Bowman & Rodger, 1972;Rodger, 1973;Houston & Rodger, 1974;Davey, Malta & Raper, 1974). Our results are consistent with this conclusion.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Other workers have found that the selectivity of P2adrenoceptor agonists is lower in the cat than in other laboratory species, for example the guinea-pig (Bowman & Rodger, 1972;Rodger, 1973;Houston & Rodger, 1974;Davey, Malta & Raper, 1974). Our results are consistent with this conclusion.…”
Section: Discussionsupporting
confidence: 93%
“…In this study the actions of a wide variety of /3adrenoceptor agonists and of two P-adrenoceptor antagonists have been determined in a single species simultaneously on bronchial muscle, soleus muscle, blood pressure and heart rate. The cardiovascular and soleus muscle actions of three of the agonistssalbutamol, orciprenaline and trimetoquinolhave been described previously (Bowman & Nott, 1970;Apperley & Daly, 1972;Houston & Rodger, 1974). Our results agree closely with those of the previous reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…at the beginning and end of inspiration). Details are given in the paper by Houston & Rodger (1974).…”
Section: Methodsmentioning
confidence: 99%
“…In view of this association of effects of sympathomimetic amines on the cat soleus and on slow motor units in man, the cat soleus preparation has been used to predict the tremorogenic activity of 0-adrenoceptor agonists in man. It is used in particular in the pre-clinical assessment of sympathomimetic bronchodilators, and its value in this respect has been substantiated by a correlation between the potencies of drugs in depressing the cat soleus (Bowman & Nott, 1970;Gwee et al, 1972;Houston & Rodger, 1974) and in causing tremor in man (Watson & Richens, 1974;Marlin & Turner, 1975). Because of its typical 0-adrenoceptor-mediated depressant action on the soleus, THP is thus likely to exert direct tremorogenic actions on muscle fibres of slow motor units in man.…”
Section: Discussionmentioning
confidence: 99%